2023
DOI: 10.48084/etasr.5607
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a Circular Footing resting on Sand Reinforced with Geogrid and Grid Anchors

Abstract: This study used finite element analysis to investigate the influence of using two reinforcing systems, the geogrid and the grid anchor, on the bearing capacity of a circular footing resting on sand. The parameters studied were the effect of the number of reinforcement layers (N), the depth ratio of the topmost layer of reinforcement (u/d), the vertical spacing ratio between consecutive layers (h/d), and the effect of reinforcement length (L). The results showed that the reinforcement layout had a very signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Komolafe et al [28] investigated the square and circular footings supporting on cohesionless soils from a structural, geotechnical and construction cost perspective. Helis et al [29] estimated the bearing capacity of a circular footing supported on sand using two reinforcing systems, the geogrid and the grid anchor.…”
Section: Introductionmentioning
confidence: 99%
“…Komolafe et al [28] investigated the square and circular footings supporting on cohesionless soils from a structural, geotechnical and construction cost perspective. Helis et al [29] estimated the bearing capacity of a circular footing supported on sand using two reinforcing systems, the geogrid and the grid anchor.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional rehabilitation of embankments and cut slopes sometimes requires removing slide debris and replacing it with freedraining granular materials. An alternative restoration method uses geosynthetics (geotextiles or geogrids) as reinforcement to reduce stabilizing costs [4][5]. In past, the performance of a geotextile-reinforced slope and its causes of failure was assessed using centrifuge testing procedures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sireesh et al [25]; El-Sawwaf and Nazir [26]; Demir et al [27]; Chakraborty and Kumar [20]; Tafreshi et al [28]; Sharma and Kumar [29]; Hosamo et al [30]; Ameer and A'amal [31]; Jawad et al [32]; Helis et al [33]). Boushehrian and Hataf [22] conducted experimental and numerical studies to examine the impact of the initial layer's depth of reinforcement, vertical spacing, and number of reinforcement layers on the bearing capacity of circular and ring footings.…”
mentioning
confidence: 99%
“…They concluded that the optimum diameter ratio is 0.25, and the optimum depth of the topmost reinforcement layer as well as the optimum vertical depth between layers are around 0.25 times of the footing diameter at which the maximum improvement in bearing capacity is achieved. Helis et al [33] used finite element analysis to investigate the bearing capacity of a circular footing on sand bed reinforced by two different reinforcement systems, geogrid and grid anchor. The optimum length of the reinforcement was determined to be 5 times of the footing diameter for both geogrid and grid anchor systems, and the optimal depth of the first…”
mentioning
confidence: 99%